HUBUNGAN HIRARKI DALAM PERUNDANG-UNDANGAN KETENAGAKERJAAN” (Studi Normatif Mengenai Peraturan Daerah Perlindungan Ketenagakerjaan Di Indonesia) - Andari Yurikosari (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
Basically Act No. 13 of 2003 on Manpower has set up various terms of employment especially legal protection for workers in terms of labor relations and labor protection. Various regulation as the Implementing Regulations of Law No. 13 Year 2003 on Manpower has also been set up on the technical aspects of the implementation of legal protection in employment relations for workers, especially workers attached to the Employment Agreement Specific Time (PKWT). By obstacles encountered in practice its implementation is in the legislation and district regulation are not dealt with decisively on sanctions, even if arranged on a change 'void' of a violation of the regulation clauses regarding PKWT into Employment Agreement for Unspecified Time (PKWTT) remain  inside the practice of many violations. This study uses normative research by reviewing the legal materials in the form of Act No. 13 of 2003 on Labour and Employment District Regulation of Subang district, Pasuruan, Karawang, Bekasi City and Depok City. Talking about phrase 'void' own, some circles and legal experts debate on this matter. In the Article 59 paragraph (7), Article 65 Paragraph (8) and Article 66 paragraph (4) of Law No. 13 Year 2003 on Manpower contained the phrase 'void'. The phrase is closely related to the conditions that must be met in a change in the status of the employment agreement specified time become employment agreement for an unspecified time and the status of outsourcing workers. Act No. 12 of 2011 has set the sort order of hierarchy or regulations in Indonesia Article 7 Paragraph (1) are arranged in a hierarchy that the Constitution occupies the highest position in the hierarchy and District Regulations lowest ranks in the hierarchy. District Regulation function as the implementing regulations of the law in every region is different from each other, each due also to the regional autonomy that makes one different regional needs with the needs of other regions. Relating to Law No. 13 of 2003 on Labour, in various regions both in the provincial capital as well as in the district or the city, the local government drafting regional regulations, especially concerning the implementation and application of administrative sanctions in case of violation of the Act setting PKWT in Act Number 13 Year 2003 on Manpower. In general, while the assessment of the results of initial studies normative for District Regulations on Employment in force in various regions in Indonesia, eventually encountered many regional regulations are ineffective and inefficient because of the articles contained in the set has its laws. District Regulation itself should contain about things that are not regulated in the substance of the legislation (the substance of the rest) because it is basically made as a District Regulation verordnung and autonome satzung (implementing regulations)) Keywords: district regulation, employment agreement